Analysis of Internal Control Over Financial Reporting Based on Liquidation at Banks in Liquidation According to the COSO Internal Control Framework: A Case Study of the Deposit Insurance Corporation - Irfan Yuansyah; Ludovicus Sensi Wondabio (Green Publisher Indonesia, 2026)
This research examines the effectiveness of internal controls over transaction recording and liquidation-basis financial reporting in Banks in Liquidation (BDL), using the COSO Internal Control–Integrated Framework and a qualitative case study of the Indonesia Deposit Insurance Corporation (LPS). Despite the critical role of liquidation-basis reporting in safeguarding creditor rights and ensuring accountability, empirical research in this domain remains limited, particularly regarding controls surrounding credit asset realization and valuation. Data were collected through document analysis, business process mapping, development of a risk control matrix (RCM), and semi-structured interviews with liquidation teams, supervisory units, risk management functions, and external auditors. Analysis across six core liquidation processes reveals that LPS has implemented multiple entity-level and transaction-level controls; however, several control deficiencies persist, including the absence of detailed technical standard operating procedures, inconsistent documentation, limited formal risk assessment practices, suboptimal use of information systems, and gaps in ongoing monitoring. Although these deficiencies do not constitute material weaknesses, they may undermine the reliability of key financial reporting assertions, particularly existence, completeness, and valuation of credit assets. The study contributes to the literature by extending internal control research into the underexplored context of liquidation-basis reporting and provides theoretical insights through stewardship and agency perspectives. Practical implications include recommendations for LPS to strengthen SOP standardization, enhance liquidation team competencies, and reinforce monitoring mechanisms. The findings offer empirical guidance for improving the governance, transparency, and reliability of financial reporting in bank liquidation settings.